Antimutagenic properties of basil (Ocimum basilicum L.) in Salmonella typhimurium TA100 - Stajković, Olivera (Array, 2007)
The use of dietary antimutagens and anticarcinogens has been seen as a promising approach to the protection of human health. Basil (Ocimum basilicum L.) is a well-known medicinal and aromatic plant, with a range of newly discovered biological activities possibly important for chemoprevention. In the preliminary experiments, toxic and mutagenic potential of essential oil (EO) from basil and pure substances: linalool, ß-myrcene and 1,8- -cineole were tested using Salmonella typhimurium TA98, TA100 and TA102, with and without S9 mix (microsomal fraction of rat liver). No mutagenic effect of basil derivatives was detected in any tested strain. Antimutagenic effects of essential oil from basil and its pure constituents were further evaluated in the Ames test using S. typhimurium TA100. UVC irradiation and three chemical mutagens, 4-nitroquinoline-N-oxide (4NQO), 2-nitropropane (2-NP) and benzo(a)pyrene (B(a)P) were used to induce mutagenesis. All tested basil derivatives significantly reduced UV-induced mutations. The maximum inhibition was in the range of 64–77 %. Inhibitory potential against direct acting model mutagen/carcinogen 4NQO was similar to UV (52–67 %). In the presence of S9, EO and 1,8-cineole showed moderate inhibition of 2-NP induced mutagenesis, while the remaining two substances had no effect